POTRET MEKANISME PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN SIMPAN PINJAM PEREMPUAN (PNPM MPd SPP) DI DESA BUKIT LEMBAH SUBUR KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Wiwin Ida Sari; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This thesis is proposed to fulfill undergraduate requirement of sociology science. The title of this thesis is “Portrait of Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan Simpan Pinjam Perempuan (PNPM MPd-SPP) in Desa Bukit Lembah Subur Kecamatan Kerumutan Kabupaten Pelalawan”. This thesis shows us the recipien characteristics PNPM fund and also shows us the difference of social and economic after joining PNPM. Population of this research are the recipien of PNPM MPd-SPP fund in Desa Bukit Lembah Subur. Sampling was done by purposive technique sampling. In this technique, people who are about to be research subject is decided by writer. The number of population is 117 (year 2012-2013). Total of sample is 45 people. Writer used descriptive quantitative method with quantitative and qualitative analysis. Data instrument are observation, questionaire, and interview. Data tabulation is single data and diagram. Result shows that the recipien of PNPM SPP fund recipien in Desa Bukit Lembah Subur are mostly married women and have business. Mostly respondents are about 38 years old, elementary level of education, and enterpreneur. They generally have 3-5 family member, join PNPM on 2008, and having husband who are a farmer. The data of social and economic of society member change. The income grow among them, but the willingness to participate in social activities is poor. Yet they have such a good care about social charity. Last, they tend to have lack of family interaction.Key word: mechanism, PNPM, Simpan Pinjam Perempuan (SPP)